2007
DOI: 10.1109/iembs.2007.4352798
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photodiode for Reflectance Pulse Oximetry in low-power applications

Abstract: Abstract-The amount of light collected is crucial for lowpower applications of pulse oximetry. In this work a novel ring-shaped backside photodiode has been developed for a wearable reflectance pulse oximeter. The photodiode is proven to work with a dual LED with wavelengths of 660 nm and 940 nm. For the purpose of continuously monitoring vital signs of a human, a temperature sensor is integrated onto the chip containing the photodiode. This biomedical multisensor chip is made for integration into "the Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…One of the other ways to increase the area of the photoreceptor is to use a ring shape photoreceptor introduced in [33]. In this work, as it is shown in Figure 15, a ring shaped photodiode has been developed for a wearable reflection pulse oximeter.…”
Section: Leds and Photoreceptormentioning
confidence: 99%
“…One of the other ways to increase the area of the photoreceptor is to use a ring shape photoreceptor introduced in [33]. In this work, as it is shown in Figure 15, a ring shaped photodiode has been developed for a wearable reflection pulse oximeter.…”
Section: Leds and Photoreceptormentioning
confidence: 99%
“…Pulse oximetry relies on the difference in the absorption spectra between oxygenated haemoglobin (HbO 2 ) and deoxygenated haemoglobin (Hb). In [9] it is shown that the ratio between absorption coefficients of HbO 2 and Hb makes wavelengths of 660 nm and 940 nm suitable.…”
Section: Pulse Oximetry Applicationmentioning
confidence: 99%
“…In this paper we report the recent development of a patient monitoring system the "Electronic Patch" shown in Fig. 1 which we previously have proposed [8], [9]. The patch can monitor various physiological signals, analyze these and when needed either transmit an alarm or continuously stream data over a wireless network.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the design and development of an Electronic Patch with integrated reflective pulse oximetry based on a novel ring-shaped optical sensor [1], [2], [3]. The Electronic Patch is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%